2012
DOI: 10.3758/s13423-012-0262-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perspective and goals on reference production in conversation

Abstract: we evaluated a new hypothesis-that the relevance of the addressee's perspective depends on the speaker's goals. In two experiments, Korean speakers described a target object in situations in which the perspective status of a competitor object (e.g., a large plate when describing a smaller plate) was manipulated. In Experiment 1, we examined whether speakers would use scalar-modified expressions even when the competitor was hidden from the addressee. The results demonstrated that information from both the speak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 24 publications
11
59
1
Order By: Relevance
“…However, the availability of privileged information also led to the production of utterances that did not take this perspective difference into account. These findings are in line with previous studies using similar paradigms (Wardlow Lane et al, 2006;Yoon et al, 2012). Interestingly, speakers even failed to completely ignore privileged information when it harmed communication (i.e.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, the availability of privileged information also led to the production of utterances that did not take this perspective difference into account. These findings are in line with previous studies using similar paradigms (Wardlow Lane et al, 2006;Yoon et al, 2012). Interestingly, speakers even failed to completely ignore privileged information when it harmed communication (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…In line with previous studies using similar paradigms (Wardlow Lane et al, 2006;Yoon et al, 2012), we found that speakers cannot completely ignore privileged information during language production and that the availability of privileged information can lead to the production of utterances that do not take the addressee's visual perspective into account. However, we found no evidence that adapting to your addressee's visual perspective requires additional planning time, suggesting that audience design is not necessarily effortful.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…"), they avoided scalar adjectives that were unnecessary for identification from a listener point of view. Contrastingly, when they had to describe events (inform the addressee, e.g., "The experimenter will move the plate to the left"), they referred to the size of the object more frequently (Yoon, Koh, & Brown-Schmidt, 2012).…”
Section: Communicative Purposes and Referring Expressionsmentioning
confidence: 99%